2016
DOI: 10.1155/2016/1643762
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Escherichia coli Strains Isolated from Alouatta spp. Feces to Essential Oils

Abstract: This study evaluated the in vitro antibacterial activity of essential oils from Lippia graveolens (Mexican oregano), Origanum vulgaris (oregano), Thymus vulgaris (thyme), Rosmarinus officinalis (rosemary), Cymbopogon nardus (citronella), Cymbopogon citratus (lemongrass), and Eucalyptus citriodora (eucalyptus) against Escherichia coli (n = 22) strains isolated from Alouatta spp. feces. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined for each isolate using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
2
15
0
3
Order By: Relevance
“…patterns were found for both species investigated in this study. The concentrations found are in accordance to previous studies (Burt et al, 2016;Pei, Zhou, Ji, & Xu, 2009) and were lower than the ones found for others essential oils (oregano, thyme and clove) tested against the same species (Lara et al, 2016;Solarte et al, 2018). Furthermore, MIC and MBC values almost coincided (two-fold difference), which indicates that CNMA killing is generally bactericidal, a highly desirable mode of action to control microbial contamination (Ocampo et al, 2014).…”
Section: Antimicrobial Activity Of Cnma Towards Planktonic Cultures Osupporting
confidence: 90%
“…patterns were found for both species investigated in this study. The concentrations found are in accordance to previous studies (Burt et al, 2016;Pei, Zhou, Ji, & Xu, 2009) and were lower than the ones found for others essential oils (oregano, thyme and clove) tested against the same species (Lara et al, 2016;Solarte et al, 2018). Furthermore, MIC and MBC values almost coincided (two-fold difference), which indicates that CNMA killing is generally bactericidal, a highly desirable mode of action to control microbial contamination (Ocampo et al, 2014).…”
Section: Antimicrobial Activity Of Cnma Towards Planktonic Cultures Osupporting
confidence: 90%
“…The second stage. E. coli resistance test against some antibiotics were used dilution method, namely Minimum Inhibitory Concentration (MIC) 20 and Minimum Bacteriocide Concentration (MBC). The test were done through several antibiotics: amoxicillin, amphicillin, erythromycin, cephalosporins, tetracycline, cloxacilin and gentamicin.…”
Section: Methodsmentioning
confidence: 99%
“…Reports have also suggested the antioxidative and anticancer activities of lemongrass as well (5, 6, 12-14, 22, 40, 44). Several others also indicated that lemongrass essential oil (LGEO) shows potent antibacterial activity on several microorganisms, including E. coli, Sterptococus pyonenes, and Pseudomonas fluorescence (10,23,25,26,37,50,56,58). In this study, we investigated anti-NoV activity of LGEO both in vitro and in vivo.…”
mentioning
confidence: 97%